Listeria monocytogenes Colonizes Pseudomonas fluorescens Biofilms and Induces Matrix Over-Production - Puga, Carmen H.; Dahdouh, Elias; SanJose, Carmen; Orgaz, Belen (Frontiers in Microbiology, 2018)
In food facilities, biofilms or their debris might act as helpers for attracting free floating microorganisms. In this sense, Pseudomonas fluorescens, a dense biofilm producer frequently isolated from food contact surfaces, could be a good candidate for sheltering other microorganisms, such as Listeria monocytogenes. The main objective of this work was to evaluate the ability of L. monocytogenes to colonize pre-established Pseudomonas biofilms. For this, the movement throughout mature Pseudomonas biofilms of a Green Fluorescent Protein (GFP) - tagged strain of L. monocytogenes was tracked for 24 h by Confocal Laser Scanning Microscopy (CLSM). Moreover, in order to check the effect of the incorporation of Listeria on the overall matrix production, attached populations of both microorganisms and total biomass (cells + matrix) of the resulting biofilms were measured over time. Planktonic cells of L. monocytogenes efficiently migrated to preformed P. fluorescens biofilms. Moreover, they moved preferentially towards the bottom layers of these structures, suggesting some kind of tropism. When preformed P. fluorescens biofilms were conditioning the surfaces, the L. monocytogenes attached population was on average, 1-2 Log higher than when this organism grew on bare coupons. Furthermore, the arrival of L. monocytogenes to the already established P. fluorescens biofilms led to a matrix over-production. Indeed, biomass values (optical density, OD595nm) of the resulting biofilms were double those of the ordinary L. monocytogenes-P. fluorescens mixed biofilms (1.40 vs. 0.6). The fact that L. monocytogenes cells accumulate in the bottom layers of preformed biofilms provides this microorganism an extra protection towards physical-chemical damages. This might partly explain why this microorganism can persist in food industry environments.